2019
DOI: 10.1111/hae.13802
|View full text |Cite
|
Sign up to set email alerts
|

Advanced magnetic resonance imaging of cartilage components in haemophilic joints reveals that cartilage hemosiderin correlates with joint deterioration

Abstract: Introduction: Evidence suggests that toxic iron is involved in haemophilic joint destruction. Aim:To determine whether joint iron deposition is linked to clinical and imaging outcomes in order to optimize management of haemophilic joint disease. Methods: Adults with haemophiliaA or haemophilia B (n = 23, ≥ age 21) of all severities were recruited prospectively to undergo assessment with Hemophilia Joint Health Scores (HJHS), pain scores (visual analogue scale [VAS]) and magnetic resonance imaging (MRI) at 3T u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…In addition, the clearance of haemosiderin‐laden macrophages and the normalization of synovial fluid cellular composition were also evidenced. These findings are in agreement with previous reports that indicate that the presence of intracellular haemosiderin deposits in cartilage and synovium is associated with joint deterioration in patients with haemophilia 28,29 . Moreover, the macrophages haemosiderin‐intracellular vesicles could remain stables during weeks even after reduction of free iron overload 23 .…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the clearance of haemosiderin‐laden macrophages and the normalization of synovial fluid cellular composition were also evidenced. These findings are in agreement with previous reports that indicate that the presence of intracellular haemosiderin deposits in cartilage and synovium is associated with joint deterioration in patients with haemophilia 28,29 . Moreover, the macrophages haemosiderin‐intracellular vesicles could remain stables during weeks even after reduction of free iron overload 23 .…”
Section: Discussionsupporting
confidence: 93%
“…Surgery yielded multiple pieces of bone tissue from the femur, patella, and tibia, including some attached hypertrophic synovium. The tissues were fixed in 10% formalin (3.7% formaldehyde) for 48 h and decalcified in 10% formic acid including 0.2% K 4 Fe(CN) 6 to allow the Perl’s reaction during decalcification 32 . Resulting tissue was stained blue in iron‐rich locations and was dehydrated and embedded in paraffin.…”
Section: Methodsmentioning
confidence: 99%
“…The tissues were fixed in 10% formalin (3.7% formaldehyde) for 48 h and decalcified in 10% formic acid including 0.2% K 4 Fe(CN) 6 to allow the Perl's reaction during decalcification. 32 Resulting tissue was stained blue in iron-rich locations and was dehydrated and embedded in paraffin. A total of 6-to 8-μm sections were counterstained with hematoxylin under acidic conditions for a red nuclear counterstain, and imaged on an Olympus AH-2 microscope with a 2.5× objective.…”
Section: Histologymentioning
confidence: 99%
“…85 Iron accumulation in cartilage is another biomarker that has been shown to correlate with joint damage and progression of hemophilic arthropathy, further it has the advantage of being easily detected with MRI T2* sequences. 86 The development and validation of iron quantification MRI methods could assist in detecting asymptomatic joint bleeding, and provide a tool to evaluate and adjust treatment in patients with hemophilia. 86 Vascularization and angiogenesis have been found to be increased in patients with joint damage.…”
Section: Dovepressmentioning
confidence: 99%
“…86 The development and validation of iron quantification MRI methods could assist in detecting asymptomatic joint bleeding, and provide a tool to evaluate and adjust treatment in patients with hemophilia. 86 Vascularization and angiogenesis have been found to be increased in patients with joint damage. One study found that proangiogenic factors and proangiogenic macrophage/monocyte cells were up-regulated in patients with joint disease and expression of VEGFR2/AC133 endothelial progenitor cells and CD34/VEGFR1 hematopoietic progenitor cells were increased.…”
Section: Dovepressmentioning
confidence: 99%